Historiography of the construction of Sherdor and Tillakori madrasahs (1619-1660 years) - Imamov Ulug’bek Ismailovich (Periodica Journal, 2023)
Yalangtosh Bahadir, who was the mayor of Samarkand in 1626 - 1656, has not yet been considered in the field of historiography of the architecture of Uzbekistan in connection with the architecture of that time. This is because the history of our country did not have more complete information about this person. In honor of our independence, the history of all persons related to the city of Samarkand is thoroughly studied, in particular, the history of Yalangtosh Bahadir was also studied by the scientists of Samarkand State University E. Musurmonov, T. Joraev. Among those who ruled the city of Samarkand, there are many rulers who contributed to the development of architecture and improvement of the city, its architecture and urban environment. The most famous of them are Amir Temur and Mirza Ulugbeks, as well as Ibrahim ibn Nasr Tamgach Khan Karakhani (1040-1070), Yalangtosh Bahadir (1576- 1656) and Samarkand bek Shahmurad ibn Daniyal can be included in their ranks
Keywords: Madrasah; hujra; dome